2009
DOI: 10.1038/ajh.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17-Hydroxyprogesterone on Tumor Necrosis Factor- -Induced Hypertension During Pregnancy

Abstract: BACKGROUND Inflammatory cytokines such as tumor necrosis factor-α (TNF-α) may be an important link between placental ischemia and hypertension in preeclampsia. We examined the effect of 17-hydroxyprogesterone caproate (17-OHP) on TNF-α-stimulated endothelin (ET) production and hypertension during pregnancy. METHODS TNF-α-stimulated ET was examined from endothelial cells cultured in the presence and absence of progesterone. Blood pressure and tissue ET-1 were measured in the following groups of pregnant rats:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…To further assess the chronic interactions between of TNF-␣ and sFlt-1, we also examined the chronic effect of TNF-␣ infusion into NP rats on plasma sFlt-1 levels. Recombinant, purified rat TNF-␣ (BioSource International, Morrisville, NC) was infused via miniosmotic pump into NP rats at a rate of 50 ng/day for 5 days beginning on day 14 of gestation, as previously described by our laboratory (14,26). This rate of infusion is comparable to the increase in serum TNF-␣ in our RUPP model of placental ischemia (18).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…To further assess the chronic interactions between of TNF-␣ and sFlt-1, we also examined the chronic effect of TNF-␣ infusion into NP rats on plasma sFlt-1 levels. Recombinant, purified rat TNF-␣ (BioSource International, Morrisville, NC) was infused via miniosmotic pump into NP rats at a rate of 50 ng/day for 5 days beginning on day 14 of gestation, as previously described by our laboratory (14,26). This rate of infusion is comparable to the increase in serum TNF-␣ in our RUPP model of placental ischemia (18).…”
Section: Methodsmentioning
confidence: 98%
“…Moreover, hypoxia stimulated a twofold increase in TNF-␣ (4) and sFlt-1 (27) from NP human placental explants. More recent data from our laboratory shows plasma and placental levels of sFlt-1 (11) and TNF-␣ (18) to be significantly elevated in response to reduced uterine perfusion pressure (RUPP) and TNF-␣-induced hypertension in pregnant rats (14). While these data suggest a link between the enhanced production of TNF-␣ and sFlt-1 in response to placental ischemia and/or hypoxia, the importance of TNF-␣ in stimulating sFlt-1 production is unknown.…”
mentioning
confidence: 96%
“…After binding to the TNF-α receptor on the cell membrane of VECs, TNF-α exerts its biological effect via multiple pathways (11)(12)(13)(14)(15) to induce inflammation and alter coagulant/fibrinolytic function of VECs (16), leading to inflammation and coagulation. In the present study, a TNF-α-induced VEC injury model was established to investigate alterations in cell morphology and subcellular structures.…”
Section: Discussionmentioning
confidence: 99%
“…They further showed that in patients receiving 17-OHPC there was reduced cervical shortening. 14 Keiser et al 26 showed in a rat model that 17-OHPC attenuated the effect of TNF-a-induced hypertension by reducing the production of endothelin. Veillon et al 27 showed normalization of TNF-a and IL-6 in response to placental ischemia with the administration of 17-OHPC to rats.…”
Section: Discussionmentioning
confidence: 99%